2016
DOI: 10.1007/s11121-016-0725-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Cognitive Behavioral Therapy-Based Indicated Prevention Program for Children with Elevated Anxiety Levels: a Randomized Controlled Trial

Abstract: Childhood anxiety is a problem not only because of its negative consequences on the well-being of children but also because of its adverse effects on society and its role in mental disorders later in life. Adequate prevention might be the key in tackling this problem. The effectiveness of Coping Cat, as an indicated CBT-based prevention program in Dutch primary school children, was assessed by means of a randomized controlled trial. In total, 141 children aged 7–13 with elevated levels of anxiety and their mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
4
21
0
Order By: Relevance
“…In trials assessing non-inferiority, it is essential that the effect of the gold standard—in this case CBT—is comparable to previous trials. Accordingly, in the current study, the CBT condition yielded effects in line with a previous indicated prevention trial (van Starrenburg et al 2017 ). Furthermore, efficacy results for MindLight were comparable to those of an initial RCT (Schoneveld et al 2016 ).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In trials assessing non-inferiority, it is essential that the effect of the gold standard—in this case CBT—is comparable to previous trials. Accordingly, in the current study, the CBT condition yielded effects in line with a previous indicated prevention trial (van Starrenburg et al 2017 ). Furthermore, efficacy results for MindLight were comparable to those of an initial RCT (Schoneveld et al 2016 ).…”
Section: Discussionsupporting
confidence: 88%
“…The equivalence margin for improvement in anxiety score was set at 0.16 SCAS points. This difference corresponds to 0.5 SD of the anxiety change score ( M = 0.14, SD = 0.32) at post-test in children allocated to CBT, as found in a previous indicated prevention RCT (van Starrenburg et al 2017 ). Based on 80% power (1 − β) to detect a clinically relevant difference in improvement of 0.16 points on the SCAS ( α = .05, two-sided), 50 children were required in each group.…”
Section: Methodssupporting
confidence: 73%
See 2 more Smart Citations
“…Sensitivity to treatment effects: Significant effect for treatment versus wait list control or treatment as usual for SCAS‐C and SCAS‐P (Arendt, Thastum, & Hougaard, ; Cobham, ; Wuthrich et al., ). SCAS‐C (Barrett, Farrell, Ollendick, & Dadds, ); Child but not parent effects (van Starrenburg, Kuijpers, Kleinjan, Hutschemaekers, & Engels, ). Parent but not child effects (Donovan, Cobham, Waters, & Occhipinti, ; Vigerland et al., )…”
Section: Evidence‐based Measures/psychometric Criteria – What Do We Lmentioning
confidence: 99%